Diffusive spectra of antistokes wing of photoluminescence of carbon nanostructures - Kumekov, S.E.; Saitova, N.K. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
In paper the photoluminescence radiation with a wavelength shorter than the wavelength of the exciting light that usually have been called anti-Stokes, is studied. These features of photoluminescence were observed previously in such carbon-containing objects as amorphous hydrogenated carbon α-C: H and native biopolymer-collagen. The general structural property of these objects is the presence of carbon hexagons — the nuclei of the benzene ring. A dimer-excimer model of photoluminescence in carbon nanostructures was developed to explain the anti-Stokes wing of the spectra. The temperature dependence of the distribution function of thermally activated pre-excited states in carbon-containing objects is determined. The spectral dependence of the intensity of the anti-Stokes wing taking into account the density of states in the excimer well is calculated.
Keywords: carbon quantum dots; photoluminescence of carbon-containing objects; anti-Stokes radiation; photodissociation; dimeric-excimer model